How Fair is Gender-Fair Language? Insights from Gender Ratio Estimations in French. (January 2023) - Xiao, Hualin; Strickland, Brent; Peperkamp, Sharon
Heated societal debates in various countries concern the use of gender-fair language, meant to replace the generic use of grammatically masculine forms. Advocates and opponents of gender-fair language disagree on – among other things – the question of whether masculine forms leave women underrepresented in people's minds. We investigated the influence of linguistic form on the mental representations of gender in French. Participants read a short text about a professional gathering and estimated the percentages of men and women present at the gathering. Results showed higher estimates of the percentage of women in response to two gender-fair forms relative to the masculine form. Comparisons with normed data on people's perception of real-world gender ratios additionally showed that the gender-fair forms removed or reduced a male bias for neutral- and female-stereotyped professions, respectively, yet induced a female bias for male-stereotyped professions. Thus, gender-fair language increases the prominence of women in the mind, but has varying effects on consistency, i.e., the match with default perceptions of real-world gender ratios.